Effect of absorber layer, hole transport layer thicknesses, and its doping density on the performance of perovskite solar cells by device simulation. (15th January 2020) - Bag, Atanu; Radhakrishnan, R.; Nekovei, Reza; Jeyakumar, R.
Highlights: An ideal thickness for absorber and hole transport layer is reported for high efficiency. An optimum doping density has been found for absorber and hole transport layers. Hole transport layer less than 50 nm or more than 200 nm are not suitable. By fine tuning parameters, an efficiency of 28.56% has been obtained. Abstract: Perovskite solar cells are high efficiency solar cells for low-cost electricity production. In this simulation work, methylammonium lead iodide based perovskite solar cells performance as a function of thickness and doping density of perovskite and hole transport layers are reported. Perovskite layer thickness is important for high performing device and there is no advantage of using thinner (<200 nm) or thicker (>700 nm) film in the device. A trade-off exists between light absorption and carrier extraction. Our result shows that when a thin layer is used, low photocurrent results due to less absorption, however carrier extraction is high. For thick perovskite layer, although more carriers are generated in the device due to an increase in absorption, lower collection efficiency is due to recombination which affects Voc . An increase in doping density in the perovskite layer enhances device performance due to built-in electric field across the device. Similar to absorber thickness, very thin or thick hole transport layer (HTL) is not suitable for high efficiency. A 100–200 nm HTL is required for less recombination and high fill factor. Doping density variation in HTL shows fill factor increase as the doping density increase, and a concentration of 5 × 10 18 /cm 3 is required for high efficiency. For an optimized device, high efficiency of 28.56% has been obtained with Voc, Jsc and fill factor of 1.29 V, 25.40 mA/cm 2 and 0.87 respectively.